2023
DOI: 10.1088/1742-6596/2518/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Modulating via External Electric Field an Electronic Band Gaps in 2D 1T-PdS2 monolayer

Abstract: We have examined structural stability and electronics properties of 2D 1T-PdS2 monolayer within the Density Functional Theory (DFT). 1T-PdS2 monolayer has indirect narrow band gap of 1.16 eV along the wave vector path of Γ-M-K-Γ in first Brillouin zone. The positive phonon dispersion curves at gamma point confirmed the dynamic stability of the 1T-PdS2 monolayer. Under the external electric field E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…It is apparent from figure 3 that the 1T-PdS 2 monolayer is an indirect bandgap semiconductor with the valence band maximum (VBM) and conduction band minimum (CBM) lying along the Γ -point and between Γ -M points, respectively. The obtained value of bandgap, E PBE , is 1.173 eV, which is quite comparable with earlier reported values, i.e., 1.11 eV [27], 1.24eV [38,54], 0.99 eV [55], and 1.16eV [44]. We have also calculated the bandgap using GGA + SOC and GGA + U (U=3.69) methods [35].…”
Section: Electronic Propertiessupporting
confidence: 89%
See 1 more Smart Citation
“…It is apparent from figure 3 that the 1T-PdS 2 monolayer is an indirect bandgap semiconductor with the valence band maximum (VBM) and conduction band minimum (CBM) lying along the Γ -point and between Γ -M points, respectively. The obtained value of bandgap, E PBE , is 1.173 eV, which is quite comparable with earlier reported values, i.e., 1.11 eV [27], 1.24eV [38,54], 0.99 eV [55], and 1.16eV [44]. We have also calculated the bandgap using GGA + SOC and GGA + U (U=3.69) methods [35].…”
Section: Electronic Propertiessupporting
confidence: 89%
“…Upon examination of figure 2(a), it is observed that all frequencies in the vicinity of Γ -point are positive, indicating the dynamical stability of the structure. However, there is some distinction in the frequency scale of present phonon dispersion spectra, as compared to the one given by Raval et al [44]. This difference may occur due to the different methodology employed for performing the calculations.…”
Section: Structure and Stabilitymentioning
confidence: 76%